The effect of the proposed teaching program in the increase of motivation to physical and sporting sessions among primary school pupils - An experimental study on pupils in the fifth year of primary education – - merwandjoubar, (sports creativity, 2025)
Summary : Title The effect of the proposed teaching program in the increase of motivation to physical and sporting sessions among primary school pupils - An experimental study on pupils in the fifth year of primary education – This study aims to determine the impact of the proposed teaching program on the increase of motivation to physical and sporting sessions in fifth year primary school pupils, and the distinction between the existence of possible statistical differences between boys and girls through this variable as a result of the application of this proposed teaching program. For this purpose, the experimental method was used using the concept of equal groups. The study was carried out on a sample of 48 students randomly selected and divided into two groups of 24 students, the first is the "experimental group" and the second "control group", each consisting of 12 boys and 12 girls attending fifth year primary school « Zighoud Youcef » of Sidi Aissa, province of M'sila. In this study, we relied on one tool in collecting data : identification of motivation to physical and sporting sessions. After verification of the scientific characteristics of the tool, they were previously applied to the two groups, then the experimental group was subjected to the experimental variable of the proposed teaching program, when control group has received regular physical and sport education sessions ( regular sessions). This tool was applied later on the two groups, and the following results were then observed: - The application of the proposed teaching program has a positive impact on the increase of motivation to physical and sporting sessions in the fifth year primary school pupils. - The absence of statistically significant differences attributed to the gender factor in the application of the proposed teaching program in increase of motivation to physical and sporting sessions for fifth year primary school pupils.